2002
DOI: 10.2519/jospt.2002.32.9.461
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Detect Dexamethasone Phosphate in the Local Venous Blood Postcathodic Iontophoresis in Humans

Abstract: Study Design: A single-blind, 2-factor (4 treatments by 8 time points) repeated-measures study design. Objective: To analytically determine dexamethasone and dexamethasone phosphate concentrations in plasma derived from proximal effluent venous blood, following cathodic iontophoresis. Methods and Measures: Six volunteers received the following dexamethasone phosphate (2.5 ml, 4 mg/ml) treatments to their wrists on separate occasions: cathodic iontophoresis (4 mA, 10 minutes or 4 mA, 20 minutes), passive applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Indeed, other studies demonstrated that iontophoresis formed a depot of the medication at the epidermal and dermal planes. 14,24,25 Using a different paradigm, Smutok et al 26 showed limited depth of penetration of dexamethasone following iontophoresis over the wrist of healthy subjects. Those investigators could not detect a measurable concentration of dexamethasone in the proximal effluent venous blood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies demonstrated that iontophoresis formed a depot of the medication at the epidermal and dermal planes. 14,24,25 Using a different paradigm, Smutok et al 26 showed limited depth of penetration of dexamethasone following iontophoresis over the wrist of healthy subjects. Those investigators could not detect a measurable concentration of dexamethasone in the proximal effluent venous blood.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in our methods from those of previous studies 14,15,30 allowed us to monitor several time points of the transdermal drug delivery of Dex-P during iontophoresis to characterize the rate of accumulation of Dex-total in human tissue. First, the present study used a longer iontophoresis dose than that used in the majority of studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, researchers have used indirect methods, such as assessing skin blanching characteristics 2 and venous blood draws, 30 to examine Dex-P delivery. One group of researchers directly measured the concentration of Dex-P in underlying tissues after an iontophoresis treatment using tissue biopsies.…”
mentioning
confidence: 99%
“…Mechanistic studies such as this which attempt to support efficacy of the use of iontophoresis to deliver DSP across the skin have used a large variety of technical approaches for estimation of the amount of DSP delivered to the tissues (e.g., observation of cutaneous vasoconstriction, analysis of blood plasma, mass spectrometry assay of extracted connective tissue, and Franz diffusion cells) . The current study is the first to use microdialysis to determine dermal concentration levels of DSP.…”
Section: Discussionmentioning
confidence: 99%